Trend of Intravitreal Bevacizumab Dispensing Technique in Nepal - Rijal, Roshija Khanal; Mourya, Deepesh; Bajimaya, Sanyam; Srivastava, Anil Kumar (Nepalese Journal of Ophthalmology, 2021)
Introduction: The main purpose of this survey was to find out what technique for bevacizumab injection is practiced by ophthalmologists in Nepal and to evaluate which is the best technique of drug dispensing and what possible hindrances are there in following it. Materials and methods: This was an online survey using google forms. Results: There were a total of 34 participants in the survey. Most of the participants (58.8%) followed the same vial, multiple prick, multiple days method for giving intravitreal bevacizumab.. Majority of participants said they thought that aliquoting the drug and using it same day would be the best technique to prevent post injection endophthalmitis. Cost and unsuitability for small hospitals were the main factor preventing surgeons from practicing the best method. Conclusion: Risk of endophthalmitis can be reduced by following proper drug dispensing techniques. Aliquoting bevacizumab in smaller syringes under aseptic conditions can reduce the risk of endophthalmitis.